2013
DOI: 10.1093/rpd/nct197
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of natural and anthropogenic radioactivity levels in soils, rocks and water in the vicinity of Chirano Gold Mine in Ghana

Abstract: Studies have been carried out within and around the operational area of the Chirano Gold Mine Ltd of Ghana to ascertain the baseline radioactivity levels of naturally occurring radioactive materials as well as artificial radionuclides in the surface and underground mines. The analysis was carried out by using gamma spectrometry to quantify the radionuclides of interest, namely (238)U, (232)Th, (137)Cs and (40)K in soil, ore, waste rock and water samples. The average activity concentrations of (238)U, (232)Th, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
6
7
0
Order By: Relevance
“…According to UNSCEAR ( 2000 ) report, the worldwide average absorbed dose rate in air measured from terrestrial gamma radiation is 60 nGyh −1 (0.059 μGyh −1 ). By comparison, the results of the absorbed dose rates in this study compare well with the range of dose rates values reported for other countries (UNSCEAR 2000 ) as well as results from similar studies carried out in other mines in Ghana (Darko et al 2010 ; Faanu et al 2010 , 2013 , 2014 ) although the average absorbed dose rate of 80 ± 20 nGyh −1 measured in air from the study area is above the worldwide average. The reasons for the higher values of the doses for external gamma could be due to difference in geological formations as well as contribution from cosmogenic radionuclides in addition to terrestrial radionuclides as observably in Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…According to UNSCEAR ( 2000 ) report, the worldwide average absorbed dose rate in air measured from terrestrial gamma radiation is 60 nGyh −1 (0.059 μGyh −1 ). By comparison, the results of the absorbed dose rates in this study compare well with the range of dose rates values reported for other countries (UNSCEAR 2000 ) as well as results from similar studies carried out in other mines in Ghana (Darko et al 2010 ; Faanu et al 2010 , 2013 , 2014 ) although the average absorbed dose rate of 80 ± 20 nGyh −1 measured in air from the study area is above the worldwide average. The reasons for the higher values of the doses for external gamma could be due to difference in geological formations as well as contribution from cosmogenic radionuclides in addition to terrestrial radionuclides as observably in Fig.…”
Section: Resultssupporting
confidence: 89%
“…For 232 Th, the average activity concentration is 71.8 ± 2.2 Bqkg −1 in range of 35.0–116.7 Bqkg −1 and that of 40 K is 1168.3 ± 15.8 Bqkg −1 in a range of 500.0–1795.9 Bqkg −1 . The results of this study also compare with the previous study that was carried in Perseus Mining (Ghana) Ltd., (Fannu et al 2013 , 2014 ). As shown in Table 3 , the average values of the activity concentrations of 238 U and 232 Th in this study are about two times higher than the world average whilst that of 40 K is about three times higher than values in normal continental soils (UNSCEAR 2000 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, the activity concentrations of 226 Ra in the shale in this study are within the results of northern PA in the USA [35]. The difference in radioactivity levels in different areas can be attributed to differences in the local geological and geochemical conditions, especially for soil, and the specific levels are closely related to the type of parent rock [36,37]. By comparison (Table 4), all of the activity concentrations of gross-α and gross-β in the soil in this study compare well with the results of similar studies reported in the Kinta and Segamat Districts, Malaysia [27,28] and Chihuahua City, Mexico [29].…”
Section: Radioactivity Characteristics Of Soils and Rockssupporting
confidence: 62%
“…However, the activity concentrations of 226 Ra in the shale in this study are within the results of northern PA in the USA [35]. The difference in radioactivity levels in different areas can be attributed to differences in the local geological and geochemical conditions, especially for soil, and the specific levels are closely related to the type of parent rock [36,37]. …”
Section: Radioactivity Characteristics Of Soils and Rockssupporting
confidence: 61%